The planktonic community in tropical interdunal ponds (Lencois Maranhenses National Park, Maranhao State, Brazil). - Moschini-Carlos, V.; Pereira, D.; Wisniewski, M.J.S.; Pompeo, M.L.M. (My University, 2008)
The aim of this study was to characterize the LenYois Maranhenses ponds (Maranhao State, Brazil) with respect to morphometry and physical and chemical aspects of the water body, in particular, the planktonic community. LenYois Maranhenses is a tropical coastal region with sand dunes and numerous interdunal ponds, most of them temporary. Ten ponds were studied, and a nictemeral variation was carried out. They have similar physical and chemical characteristics (high temperature - 27.5 to 32.0 [degree]C, acid pH - 4.9 to 6.2, low values of dissolved nutrients, chloride - 0.75 to 1.00 mg.L[long dash]1, and electric conductivity - 18.8 to 33.2 [mu]S.cm[long dash]1, and light penetration up to the sediment). With respect to the plankton, it is likely that the different histories of colonization, the formation of the ponds, and the initial organisms, affect the species richness, density and dominance observed. The lakes were classified as polymitic and oligotrophic.